Dampak Perkembangan Jalur Transportasi Terhadap Kehidupan Masyarakat Akit di Desa Hutan Panjang, Pulau Rupat - Nenggih Susilowati (Balai Arkeologi Sumatera Utara, 2007)
AbstractThe results of interaction with other community made cultural changes and developments. As the results of the development in the transportation lane influenced the Akit community. Changes not only for the cultural social but also for the nature sphere.